2022
DOI: 10.1136/bmjopen-2021-056736
|View full text |Cite
|
Sign up to set email alerts
|

Does the trauma associated with out-of-home care transmit across generations? Evidence from the 1970 British Cohort Study during a major health pandemic

Abstract: ObjectivesChildren with experience of out-of-home care (OHC) are at an increased risk of adverse outcomes in later life, including poorer levels of psycho-social adjustment. Less is known about the intergenerational transmission of the trauma associated with OHC and psychosocial outcomes in mid-adulthood, particularly during a major health pandemic.DesignTo examine if there is evidence of intergenerational transmission of trauma associated with OHC in mid-adulthood, we used data from the 1970 British Cohort St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 39 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…This can contribute to low levels of educational qualification (Forsman, 2020; O'Higgins et al, 2017; Sebba et al, 2015), but also unemployment and a more disadvantaged socio‐economic position (Boddy et al, 2020; Buehler et al, 2000; Cameron et al, 2018; Naccarato et al, 2010; Osterberg et al, 2016), unstable relationships and earlier family formation (Botchway et al, 2014; Roberts et al, 2017; Svoboda et al, 2012) and poorer mental and physical health (Cheung & Buchanan, 1997; Martin et al, 2014; Murray et al, 2020; Rees & Stein, 2016; Stein & Dumaret, 2011). Recent research by Parsons and Schoon (2021) drawing on the nationally representative UK Millennium Cohort Study (MCS) has shown that these risk factors are indeed experienced by higher proportions of mothers with OHC experience than mothers without OHC experience, which in turn puts their children at an increased risk of low educational attainment.…”
Section: Introductionmentioning
confidence: 99%
“…This can contribute to low levels of educational qualification (Forsman, 2020; O'Higgins et al, 2017; Sebba et al, 2015), but also unemployment and a more disadvantaged socio‐economic position (Boddy et al, 2020; Buehler et al, 2000; Cameron et al, 2018; Naccarato et al, 2010; Osterberg et al, 2016), unstable relationships and earlier family formation (Botchway et al, 2014; Roberts et al, 2017; Svoboda et al, 2012) and poorer mental and physical health (Cheung & Buchanan, 1997; Martin et al, 2014; Murray et al, 2020; Rees & Stein, 2016; Stein & Dumaret, 2011). Recent research by Parsons and Schoon (2021) drawing on the nationally representative UK Millennium Cohort Study (MCS) has shown that these risk factors are indeed experienced by higher proportions of mothers with OHC experience than mothers without OHC experience, which in turn puts their children at an increased risk of low educational attainment.…”
Section: Introductionmentioning
confidence: 99%